LITERATURE REVIEW : PENERAPAN TEKNIK MENGHARDIK PADA KLIEN YANG MENGALAMI SKIZOFRENIA DENGAN GANGGUAN PERSEPSI SENSORI : HALUSINASI - Bayu Seto Rindi Atmojo, Rohayati (AKPER Pemkab Purworejo, 2022)
Background: Schizophrenia is a mental disorder that has happened a lot and is experienced by humans who have penetrated the layers of society, one of which is hallucinations which means mental disorders in which the client has sensory perception disorders, where the client has unreal sensations including sight, sound, smell, taste, and touch where the client feels stimulation from the outside of the treatment that is fake or does not exist so that action is taken to rebuke the hallucinations, namely how to control the hallucinations experienced by oneself by refusing and ignoring them. Objective: To review the similarities and dissimilarities in the methods, samples or subjects, instrument, and the results of the five research articles. Method: The method used is descriptive using literature review technique by outlining theories, findings, research materials, similarities, and differences in each research conducted by researchers which are used as the basis for conducting a literature study. The search for articles was carried out with Google Scholar published from 2016 to 2021 which was accessed in full text in pdf format. Results: Based on the results of a literature review that has been compiled by the author, this technique can later be applied in nursing care regarding rebuking techniques to reduce the level of hallucinations in patients. Conclusion: The application of rebuking techniques can be applied in overcoming nursing problems in clients who experience mental disorders with sensory perception disorders: hallucinations